Jump into the sky - Pearsall, Shelley (Alfred A. Knopf, 2012)
In 1945, thirteen-year-old Levi is sent to find the father he has not seen in three years, going from Chicago, to segregated North Carolina, and finally to Pendleton, Oregon,where he learns that his father's unit, the all-Black 555th paratrooper battalion, will never see combat but finally has a mission. Includes historical notes.